Análise morfológica e distribuição geográfica de Physalaemus albifrons (Spix, 1824) (Anura, Leptodactylidae, Leiuperinae) - Melo, Suélen Helena Martins (2014)
Physalaemus is the largest genus, with regard to number of species, of the subfamily Leiuperinae, the taxonomy of which has been the subject of recent studies due to the high intraspecific and low interspecific variation within the group, with patterns of variation possibly related to geographic distribution. The Physalaemus albifrons species was first collected by Johann Baptiste von Spix in 1824, and its type locality is the "Province of Bahia", even though it is distributed from Maranhão to Minas Gerais, in regions characterized by the Caatinga morphoclimatic zone in areas of transition with the Cerrado. Due to the variation in the dorsal pattern found in Physalaemus albifrons, authors have put foward the hypothesis of the species being included in a species complex, meaning there would be more species registered under a single common name. Based on this, 98 individuals were studied, associated with each sampled location by means of analysis of morphological and morphometric characters, thus redescribing the species. Physalaemus albifrons presents four intrapopulational dorsal coloration patterns, varying from homogeneously spotless; longitudinal and irregular linear dark spots; as well as dark spots in an omega-like pattern. The second tubercle next to the tibiotarsal articulation, the absence of inguinal glands and the snout-vent length from 18,1 mm to 33,8mm proved to be diagnostic features in order to differentiate Physalaemus.albifrons from other species of the genus. This species, which may also be described as being average-sized for this genus, with the head greater in width than in length; and the snout subelliptical in dorsal view. The populations presents morphological variation as to the distinction of the tympanic ring which might be visible in some individuals and indistinguishable in others, leading to the definition of two morphological groups which are unified through canonical discriminant analysis, therefore discarding the possible characterization of the species complex in Physalaemus albifrons.